SENSITIVITY ANALYSIS IN SHALE GOUGE RATIO AND FAULT PERMEABILITY MODEL FOR POST MORTEM RE-EVALUATION OF “M” CLOSURE, OFFSHORE TIMOR SEA, INDONESIA - Rahmadi Hidayat, Rahmadi Hidayat (Jurusan Teknik Geologi, 2014)
Since gas discovery in Abadi Gas Field, Offshore Timor Sea, many exploration works have been conducted in adjacent area, including “M” closure. However, no gas findings were reported in “M” closure. In order to determine post mortem evaluation of “M” closure, evaluating fault seal is critical to understand trapping mechanism uncertainty in “M” closure. This evaluation is carried out at Triassic Challis sandstone reservoir, utilizing well data to obtain volume shale properties as well as 2D seismic data to map fault throw, orientation and juxtaposition. Shale Gouge Ratio (SGR) and Fault Permeability (Kf) model will be calculated using Yielding and Manzocchi algorithm. “M” closure is a horst structure, bounded by two NNE-SSW trending vertical faults as part of extensional event in Mesozoic. Based on three sensitivity analysis conducted in this study, SGR model revealed that bounding faults in “M” closure mostly have more than 0.2 while Kf model have 0.1 mD. Utilizing reference from earlier studies, it indicates that those bounding faults are categorized as likely sealed faults. Post mortem re-evaluation suggests that fault breaching is not the main geological risk issue in “M” closure. Furthermore, opportunities for discovery in Offshore Timor Sea are still wide open. There are many undrilled tilt-block closures similar to “M” Closure which can be potential for further development by determining its position relative to hydrocarbon charge and migration pathway. Keyword: Shale Gouge Ratio, Fault permeability, Challis reservoir